Evaluation of Sodium and Potassium Soaps Prepared from Beeswax: Adding Value to Material - Adeyemi, Adewale Fatai (International Journal of Chemistry and Materials Research, 2022)
This study investigated the potential of producing quality soaps from beeswax with a view to widening its applications and providing alternative to the high demanding fats and oils. Its potassium and sodium soaps were prepared by hot method and their properties examined. The FTIR spectroscopy indicated carboxylate band at 1560.46 cm−1 for both soaps, which is, however, absent in the original beeswax, showing that metal ions associated with the COO− ions in monodendate structures. The soaps have good qualities with respect to pH, foam ability, longevity, hardness, free alkali and total fatty matter, with the potassium soap having higher qualities. The foam ability and stability of the potassium soap were comparable to those of some commercial toilet and laundry soaps. The sodium soap, however, has better lubricating properties due to its unstable foam and low water solubility. Both prepared soaps showed lower antibacterial activity than tested antiseptic soaps but displayed almost the same activity with those of tested toilet soaps. The results showed that beeswax has the potential to serve as a good alternative to the conventional fats and oils in soap industry.